1996
DOI: 10.1126/science.273.5272.226
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Atomically Flat Silver Films on GaAs with a "Silver Mean" Quasi Periodicity

Abstract: A flat epitaxial silver film on a gallium arsenide [GaAs(110)] surface was synthesized in a two-step process. Deposition of a critical thickness of silver at low temperature led to the formation of a dense nanocluster film. Upon annealing, all atoms rearranged themselves into an atomically flat film. This silver film has a close-packed (111) structure modulated by a "silver mean" quasi-periodic sequence. The ability to grow such epitaxial overlayers of metals on semiconductors enables the testing of theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
214
0
6

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 276 publications
(232 citation statements)
references
References 23 publications
12
214
0
6
Order By: Relevance
“…Smith et al found that a Ag film deposited on GaAs͑110͒ at 135 K, and subsequently annealed to room temperature, led to the formation of a film with a closepacked ͑111͒ structure modulated by a quasiperiodic superstructure. 29 The one-dimensional height modulation of the structure yielded quasiperiodically ordered rows as observed by STM. 29,30 There are similarities between the two systems in that Fibonacci sequences and the golden ratio are identified in both.…”
Section: B Comparison With Ag/ Gaas"110…mentioning
confidence: 89%
See 1 more Smart Citation
“…Smith et al found that a Ag film deposited on GaAs͑110͒ at 135 K, and subsequently annealed to room temperature, led to the formation of a film with a closepacked ͑111͒ structure modulated by a quasiperiodic superstructure. 29 The one-dimensional height modulation of the structure yielded quasiperiodically ordered rows as observed by STM. 29,30 There are similarities between the two systems in that Fibonacci sequences and the golden ratio are identified in both.…”
Section: B Comparison With Ag/ Gaas"110…mentioning
confidence: 89%
“…29 The one-dimensional height modulation of the structure yielded quasiperiodically ordered rows as observed by STM. 29,30 There are similarities between the two systems in that Fibonacci sequences and the golden ratio are identified in both. 20,30 The difference between the two structures is that one is grown on a periodic substrate and one is grown on a quasicrystal substrate; thus the Ag film develops a quasicrystalline structure in response to the periodic potential of the GaAs, and while the Cu forms a structure in response to the aperiodic potential of the quasicrystal, and is therefore "pseudomorphic."…”
Section: B Comparison With Ag/ Gaas"110…mentioning
confidence: 89%
“…However, as a prerequisite for any potential device application, we must explore the degree of metastability of such materials, namely, how far they are from their thermodynamically stable configuration. In particular, it is desirable to know the energy barrier preventing a specific metastable configuration of a given macroscopic system from reaching its thermodynamically stable state, and to identify the dominant physical factors defining the metastable state.One example of such a metastable system is Ag overlayers on a GaAs(110) surface, which can be grown atomically flat using a two-step procedure [2][3][4]. This particular growth procedure (low-temperature deposition followed by thermal annealing) allows the film to follow a special kinetic pathway and reach a fully wetting and atomically flat two-dimensional morphology, although in thermal equilibrium the Ag-GaAs system is nonwetting and minimizes the interface area by forming three-dimensional mounds [5].…”
mentioning
confidence: 99%
“…Interesting examples include the formation of optically active quantum dots and quantum-dot superlattices in Si/Ge 1 and PbSe/PbTe heteroepitaxy, 2 metallic nanowires in silicide heteroepitaxy, 3,4 or the formation of atomically smooth metal films on semiconductor surfaces. 5,6 While the formation of wires and dots appears to be driven by a classical strain relaxation mechanism, the formation of atomically-smooth metal films is often driven by quantum-mechanical confinement. 6,7 The substrate is essential in both cases because it determines the strain energy and quantum mechanical boundary conditions of the films.…”
Section: Introductionmentioning
confidence: 99%